HUBUNGAN PENDAMPINGAN SUAMI DENGAN TINGKAT KECEMASAN IBU PADA PERSALINAN KALA I DI RUANG BERSALIN RSU ISLAM KLATEN - Hamranani, Sri Sat Titi; Sari, Devi Permata; Sari, Kurnia Tanjung (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2024)
Background: The birthing process is a stressful and emotionally arousing time for the mother, childbirth is a painful and frightening time for the mother, therefore it must be ensured that every mother receives loving care during labor. The mother's care in question takes the form of emotional support from the husband so that the husband's presence beside the mother is very important during the birthing process. The effect of not having a husband's assistance during childbirth has an impact on anxiety. This study aims to determine the relationship between husband's assistance and maternal anxiety levels during the first stage of labor in the Maternity Room at RSU Islam Klaten. Method: This type of research is descriptive correlational with a cross sectional approach. The research sample was women in the first stage of labor at RSU Islam Klaten. The sampling technique uses accidental sampling. The total sample was 33 respondents. Data collection instruments used the husband's mentoring questionnaire and the ZSAS (Zung Self Rating Anxiety Scale) questionnaire. Bivariate statistical tests using Kendall Tau. Results: The research results showed that the characteristics of the respondents in this study were an average age of 28.24 ± 4.956 years, secondary education (45.5%), not working (51.5%) and primipara (54.5%), accompanied by a husband during the first stage of labor was good (90.9%), the mother's anxiety level was mild (48.5%). The results of bivariate analysis obtained a p value of 0.038 (p < 0.05). Conclusion: there is a relationship between husband's assistance and the mother's anxiety level during the first stage of labor in the Maternity Room at RSU Islam Klaten.